Can Orthodontic Treatment Be Stable 20 Years after the End of the Treatment Scheme? Treatment of a Class 2, Division 1 Malocclusion with Severe Skeletal Discrepancy and Its 20-Year Follow-Up - Domenico Aiello; Riccardo Nucera; Stefania Costa; Michele Mario Figliuzzi; Sergio Paduano (Hindawi Limited, 2021)
Class II malocclusions, after class I malocclusions, are the most frequent in the juvenile Italian population. They are most often skeletal in origin and due to mandibular retrusion. Functional devices seem to have a beneficial effect on the growth of the jaw. Long-term maintenance of the achieved results is essential for therapeutic success in any orthodontic treatment; moreover, the retention phase should last as long as possible, especially in the lower anterior sector. A female patient aged 10 years and 3 months presented a visibly convex profile and a severe mandibular retrusion. The anamnesis brought to light the habit of oral breathing and lower-lip sucking. The cephalometric analysis showed a normodivergent skeletal class II. The first treatment phase involved the use of a Bass type for 12 months at the end of the functional treatment; the second phase of fixed therapy was carried out following the principles of bioprogressive techniques. The photos at the end of treatment show an important improvement in the profile; a full class I ratio of molar and canine teeth was achieved with an excellent interarch relationship and a correction of the V-shaped upper arch. The result is occlusally and profilometrically stable after 2, 4, 5, 10, 14, and 20 years. The maintenance of a stable orthodontic result over time is the result not only of a correct and physiological occlusion but also and above all of a correct diagnosis and correct identification of problems that can cause the malocclusion itself. Flawed habits such as interposition of the lower lip and oral breathing must be intercepted and corrected early in order to correct them and not affect the long-term result of orthodontic treatment. In this case, a functional device associated with an orthodontic fixed finishing and a correct retention phase were necessary to correctly treat a second-class mandibular retrusion whose result remained stable 20 years after the end of therapy.